1985
DOI: 10.1177/019459988509300313
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Vibratory Segment in Tracheoesophageal Speakers

Abstract: The Singer-Blom tracheoesophageal puncture procedure for surgical-prosthetic voice restoration has proved to be a viable option for alaryngeal speech rehabilitation. Following tracheoesophageal puncture, occlusion of the tracheostoma shunts pulmonary air through the Blom-Singer prosthesis into the cervical esophagus. The pulmonary air passing through the cervical esophagus and into the hypopharynx causes a portion of the upper alimentary tract to vibrate in a manner similar to that of the pharyngoesophageal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
1
18
1
Order By: Relevance
“…Different methods are used to investigate the mechanism of vibration of the pharyngoesophageal segment in esophageal speakers, each one having its own value. Videofluoroscopy is the most frequently used method, 1,2,7,8 and it is considered to be the most effective for the study of the morphology and the behavior of the cricopharyngeal segment, and for the determination of the possibility that a patient will develop this type of phonation. However, the tonus of the sphincter cannot be quantified by radiographic techniques, but only with the use of manometry.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods are used to investigate the mechanism of vibration of the pharyngoesophageal segment in esophageal speakers, each one having its own value. Videofluoroscopy is the most frequently used method, 1,2,7,8 and it is considered to be the most effective for the study of the morphology and the behavior of the cricopharyngeal segment, and for the determination of the possibility that a patient will develop this type of phonation. However, the tonus of the sphincter cannot be quantified by radiographic techniques, but only with the use of manometry.…”
Section: Introductionmentioning
confidence: 99%
“…It is presumed that this is the result of the greater aerodynamic effect in the pulmonarily driven tracheoesophageal speech (9). Videofluoroscopic studies have shown that visual characteristics of the vibratory segment of tracheoesophageal and esophageal speakers are similar (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Of nine patients with irregular neoglottic vibrations, two patients had incomplete neoglottic closure with breathy voices, four patients had multiple contacts of several mucosal walls with rough voices, and three patients had tight neoglottic closure with strained voices. trusion from the posterior pharyngeal wall [2,9,10]. In 1986, Traissac et al [8] described mucosal vibration of a circular bulge in the PE segment of TE shunt speakers with voice prostheses, but failed to use images to document their findings.…”
Section: Resultsmentioning
confidence: 99%
“…Fluoroscopy only provides information concerning the anatomical position and shape of the PE segment [2,9,10]. In contrast, direct observation of the sound source by stroboscopy demonstrates the vibratory condition of the neoglottis.…”
Section: Resultsmentioning
confidence: 99%